EFEKTIVITAS DONEPEZIL TERHADAP FUNGSI KOGNITIF PASIEN TUMOR INTRAKRANIAL PASCAOPERASI - Yusril Harun,* Yunni Diansari,* Selly Marisdina,* Yuli Felistia* (Neurona Majalah Kedokteran Neuro Sains, 2020)
INTRODUCTION THERE IS STILL A LACK OF EFFECTIVE THERAPY IN IMPROVING COGNITIVE DYSFUNCTION IN INTRACRANIAL TUMOUR PATIENTS AFTER SURGERY DONEPEZIL IS AN ACETYLCHOLINESTERASE INHIBITOR THAT HAS BEEN A THERAPY OF ALZHEIMERS DISEASE AND HAS A SIGNIFICANT EFFECT ON IMPROVING COGNITIVE FUNCTION